Materialization of Love in Morrison’s Love: A Marxist Perspective - Shrivastwa, Bimal Kishore (NUTA Journal, 2020)
This article attempts to explore how human beings are controlled by the material values in the society governed by the capitalistic regime in Toni Morrison’s novel, Love where money and matter overshadows other moral and social customs. Fascination towards economic gain is the natural inclination of the human beings since all the capitalistic desires and provisions are generally dealt with money. The overall purpose of the study is to show how Toni Morrison’s dominant characters in Love, Cosey, Heed, L and Christine are much obsessed with material success in order to capture the sordid nature of materialization of human life in the commercial world. The research methodology, used to survey the unquenched material desire of human beings such as Mr. Cosey and Christine and their degradation for it, is Marxism. Christine is ready to do everything to be a capitalistic modern. The principal finding is that in the name of love, pre-menstruated girl is made to marry an old man. She is turned into a commodity item. People are seeking mammoth pleasure but they are spiritually barren, which shows money and matter over taking the realm of love and spirituality.